2003
DOI: 10.1002/bdra.10035
|View full text |Cite
|
Sign up to set email alerts
|

Zinc treatment prevents lipopolysaccharide‐induced teratogenicity in mice

Abstract: The findings of this study strongly support the hypothesis that LPS teratogenicity is mediated at least in part by MT-induced changes in maternal Zn homeostasis,which compromises fetal Zn supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
35
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 26 publications
4
35
1
Order By: Relevance
“…Pregnant mice treated with alcohol and LPS (14,28) presented with abnormalities similar to those observed in rodents fed Zndeficient diet (Յ1 mg Zn/kg diet) throughout pregnancy (29 -31). The observed abnormalities include craniofacial, neural tube, and limb bud defects (14,28 -31).…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…Pregnant mice treated with alcohol and LPS (14,28) presented with abnormalities similar to those observed in rodents fed Zndeficient diet (Յ1 mg Zn/kg diet) throughout pregnancy (29 -31). The observed abnormalities include craniofacial, neural tube, and limb bud defects (14,28 -31).…”
mentioning
confidence: 67%
“…Therefore, this change in plasma Zn pool can be likened to a transient fetal Zn deficiency with deleterious effects on the fetus. The involvement of MT in this process can be seen in studies where MT -/-(MT-1 and -2 knockout) mice exposed to alcohol or LPS on GD8 had fetuses that were morphologically unaffected by these teratogens (14,28). Our laboratory (14) has demonstrated that a single intraperitoneal injection of LPS increased liver MT by 30-fold basal from 6 to 24 h, which coincided with an 80% decrease in plasma Zn over the same time period.…”
mentioning
confidence: 82%
See 3 more Smart Citations